2011
DOI: 10.1038/ncomms1213
|View full text |Cite
|
Sign up to set email alerts
|

Climate change drives microevolution in a wild bird

Abstract: To ensure long-term persistence, organisms must adapt to climate change, but an evolutionary response to a quantified selection pressure driven by climate change has not been empirically demonstrated in a wild population. Here, we show that pheomelanin-based plumage colouration in tawny owls is a highly heritable trait, consistent with a simple Mendelian pattern of brown (dark) dominance over grey (pale). We show that strong viability selection against the brown morph occurs, but only under snow-rich winters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
236
6
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(270 citation statements)
references
References 37 publications
14
236
6
4
Order By: Relevance
“…This pigment is phototoxic [9] and its production consumes GSH, a key intracellular antioxidant [13]. Probably as a consequence, different studies conducted on birds have shown that individuals or species producing large amounts of pheomelanin present a limited capacity to cope with physiological processes or environmental conditions that generate high levels of oxidative stress [5][6][7][8]. Under our current understanding of evolutionary theory it is difficult to explain the evolution of a pigment whose production is associated with the above-mentioned physiological costs without the existence of any adaptive benefit.…”
Section: Pheomelanogenesis As An Excretory Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…This pigment is phototoxic [9] and its production consumes GSH, a key intracellular antioxidant [13]. Probably as a consequence, different studies conducted on birds have shown that individuals or species producing large amounts of pheomelanin present a limited capacity to cope with physiological processes or environmental conditions that generate high levels of oxidative stress [5][6][7][8]. Under our current understanding of evolutionary theory it is difficult to explain the evolution of a pigment whose production is associated with the above-mentioned physiological costs without the existence of any adaptive benefit.…”
Section: Pheomelanogenesis As An Excretory Mechanismmentioning
confidence: 99%
“…Furthermore, recent studies of birds suggest that the production of pheomelanin is involved in physiological trade-offs, as judged by negative relationships between the extent of integument colored by pheomelanin and brain size [5] and interspecific differences in the capacity to resist the effects of ionizing radiation linked to pheomelanic color [6]. It has also been reported that more-pheomelanic individual barn owls (Tyto alba) are particularly sensitive to physiological stress caused by corticosterone compared to less-pheomelanic birds [7], and that tawny owls Strix aluco belonging to the pheomelanic morph have lower viability during adverse environmental conditions than conspecifics belonging to the eumelanic morph [8]. In humans and mice, pheomelanin increases the photosensitization of cells to UVinduced oxidative damage [9], its content being positively related to cancer risk in humans [10].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, in contrast to Gloger's rule, we may find that individuals are heavily pigmented in colder and dryer habitats if genes encoding for the production of melanin pleiotropically regulate physiological and/or behavioral processes adapted to such habitats. This mechanism may explain why dark, melanic Pied Flycatchers (Ficedula hypoleuca; Sirkiä et al 2010) and Tawny Owls (Strix aluco; Karell et al 2011) are more sensitive to the cold than their pale conspecifics.…”
Section: Introductionmentioning
confidence: 99%
“…In two species of owl, Eurasian Scops-Owl (Otus scops) and Tawny Owl, the dark reddish morph increased in frequency during the last century in Europe, apparently as a consequence of climate warming (Galeotti et al 2009, Karell et al 2011). These observations suggest that less melanistic individuals survive better in cold FIGURE 1.…”
Section: Climate and Melanin-based Plumage Traitsmentioning
confidence: 99%
“…The gene-up approach to the microevolution of bird migration is now yielding the first successes (e.g. Karell et al 2011;Mueller et al 2011), but is still far removed from understanding the evolution and maintenance of trait variation. Apart from notable exceptions to do with rare diseases, the detection of DNA variations that explain the phenotype has been frustratingly complex (Dowell et al 2010).…”
Section: Microevolution Of Contrasting Seasonally Changing Phenotypesmentioning
confidence: 99%